2013
DOI: 10.1007/s00405-013-2386-3
|View full text |Cite
|
Sign up to set email alerts
|

Audiological and surgical evidence for the presence of a third window effect for the conductive hearing loss in DFNX2 deafness irrespective of types of mutations

Abstract: The objective of this study was to clarify the cause of the air-bone gap in incomplete partition (IP) type III cases according to the POU3F4 gene (DFNX2) mutation type. A retrospective analysis of patient medical records was done in a tertiary referral medical center. Five IP type III patients proved to be carrying a mutation in or affecting POU3F4. The hearing and the middle ear status at either exploratory tympanotomy or cochlear implantation from these DFNX2 cases was reviewed. Four of five unrelated IP typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…In IP-II and IP-III patients, the IAC does not appear to cause the pathology, and therefore, the cochlear nerve is normal in IP-II and IP-III patients [7] . Consistent with previous studies, the present study noted the presence of severe to profound MHL in all IP-III patients [12,14,15] . Among these studies, Choi et al [14] stated that the conductive component found in IP-III malformations is related to the pathologic third window.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In IP-II and IP-III patients, the IAC does not appear to cause the pathology, and therefore, the cochlear nerve is normal in IP-II and IP-III patients [7] . Consistent with previous studies, the present study noted the presence of severe to profound MHL in all IP-III patients [12,14,15] . Among these studies, Choi et al [14] stated that the conductive component found in IP-III malformations is related to the pathologic third window.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies, the present study noted the presence of severe to profound MHL in all IP-III patients [12,14,15] . Among these studies, Choi et al [14] stated that the conductive component found in IP-III malformations is related to the pathologic third window. A recent paper by Sennaroğlu [7] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…X-linked stapes gusher syndrome was first reported in 1971 [Nance et al, 1971]. It was considered as an independent disease entity in many reports [Choi et al, 2013], and the original classifications of CVMs did not include this syndrome [Jackler et al, 1987;Sennaroglu and Saatci, 2002]. In 2006, Sennaroglu et al suggested that the radiological phenotype of X-linked stapes gusher syndrome be called incomplete partition type III [Sennaroglu et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a difference in pathogenesis between X-linked stapes gusher syndrome and other types of CVM. Most CVMs are thought to be caused by arrested or aberrant development during inner ear embryogenesis, but Xlinked stapes gusher syndrome is caused by a mutation in the POU3F4 gene on the X chromosome [Choi et al, 2013]. Therefore, X-linked stapes gusher syndrome is much better considered separately from other types of CVM because of its different audiological nature and different pathogenesis.…”
Section: Discussionmentioning
confidence: 99%